2016
DOI: 10.1186/s40478-016-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 is differentially expressed in the central nervous system and myeloid cells and consistently reduced in C9orf72, MAPT and GRN mutation carriers

Abstract: A non-coding hexanucleotide repeat expansion (HRE) in C9orf72 is a common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) acting through a loss of function mechanism due to haploinsufficiency of C9orf72 or a gain of function mediated by aggregates of bidirectionally transcribed HRE-RNAs translated into di-peptide repeat (DPR) proteins. To fully understand regulation of C9orf72 expression we surveyed the C9orf72 locus using Cap Analysis of Gene Expression sequence data (CAGEseq). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 67 publications
(102 reference statements)
14
91
0
Order By: Relevance
“…For example, microglia from presymptomatic mutSOD1 mice exhibit an antiinflammatory phenotype and attenuated innate immune response compared with microglia from symptomatic mice, which are proinflammatory and exhibit toxic properties (86,87). Similar findings were demonstrated in vitro (88), suggesting that an adaptive shift in functional microglial ing since C9orf72 is highly expressed in myeloid cells, which are critically important for antigen presentation and development of autoimmunity, and loss of C9orf72 led to lysosomal accumulation and hyperactive immune responses in bone marrow macrophages (106,(109)(110)(111). The studies of C9orf72-null mice showed variability in the degree of autoantibody production and autoimmune-mediated tissue injury, indicating an environmental influence from different housing conditions that contributed to the development of autoimmunity.…”
Section: C9orf72 In Als/ftdsupporting
confidence: 63%
“…For example, microglia from presymptomatic mutSOD1 mice exhibit an antiinflammatory phenotype and attenuated innate immune response compared with microglia from symptomatic mice, which are proinflammatory and exhibit toxic properties (86,87). Similar findings were demonstrated in vitro (88), suggesting that an adaptive shift in functional microglial ing since C9orf72 is highly expressed in myeloid cells, which are critically important for antigen presentation and development of autoimmunity, and loss of C9orf72 led to lysosomal accumulation and hyperactive immune responses in bone marrow macrophages (106,(109)(110)(111). The studies of C9orf72-null mice showed variability in the degree of autoantibody production and autoimmune-mediated tissue injury, indicating an environmental influence from different housing conditions that contributed to the development of autoimmunity.…”
Section: C9orf72 In Als/ftdsupporting
confidence: 63%
“…Prior studies have also detected high levels of C9orf72 expression in the cerebellum 23, 42 . Consistent with this work, we detected C9orf72 promoter activity in both Purkinje cells and cerebellar granule cells.…”
Section: Discussionmentioning
confidence: 82%
“…However, few of them are studied in detail and are shown to play a role in early development (7). Unsurprisingly, number of antisense RNAs are implicated in many diseases (47,(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%